CONTROVERSY BETWEEN THE SANCTIONING POWEROF THE COMPTROLLER AND THE DISCIPLINARYADMINISTRATIVE PROCEDURES - Morón Polo, Juan (2022)
The relationship between the sanctioning power of the Office of the Comptroller General of the Republic (CGR) and the administrative disciplinary procedure within the framework of the Civil Service Law is analyzed. The research followed a quantitative, cross-sectionalmethodology, with a descriptive design and correlational level. Thefindings show that for 9.4% and 17.2% of the interviewees, the principle of non bis in idem is applied very poorly and poorly respectively, 60.4% is regular and 13% is efficient. It is evident that there is a strong relationship between the sanctioning power of the CGR and the administrative disciplinary procedure with a value of Chi - Pearson Square 0.000 < α = 0.05, i.e., both fulfill their purpose. However, the problem lies when a public servant is prosecuted under both regimes, generating controversy with the principles of due process and non bis in idem.